Measurement and modelling of suprathermal electron bursts generated in front of a lower hybrid antenna. (5th February 2016) - Gunn, J.P.; Fuchs, V.; Petržílka, V.; Ekedahl, A.; Fedorczak, N.; Goniche, M.; Hillairet, J.
Abstract: Measurements in the tokamak scrape-off layer show the existence of fast electrons as far as a few centimeters radially in front of a lower hybrid antenna grill, which is one order of magnitude further than earlier predictions of interaction zones not exceeding 5 mm in width (Rantamäki et al 2000 Nucl. Fusion 40 1477). The present contribution aims at understanding these experimental results on the basis of electron Landau damping in a turbulent scrape-off layer. A crucial guiding element from the experiments is the observation of temporal intermittency of the fast electron signal at positions radially away from the grill mouth at a rate comparable with the detachment rate of relatively hot and dense field-aligned plasma filaments, or 'blobs, ' from the last closed flux surface. When the dynamic character of the scrape-off layer is taken into account, transient low density and low temperature states occur during which the Landau damping can be weak enough to allow the radiated spectrum to penetrate radially deep inward. When the lower hybrid wave intercepts a dense and hot 'blob' a few cm in front of the antenna, then strong damping of the high wave number components can occur. This is the scenario we propose for explaining the generation of fast electrons far away from the grill mouth.